Remote Sensing Based Yield Model and Application to Major Exporting Countries - Franch, Belen (2019)
Belen Franch WEBINAR Using Satellite Imagery for Early Warning of Productivity Constraints Organized by the Food Security Portal (FSP) OCT 31, 2019 - 11:00 AM TO 12:30 PM EDT